(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the concept of international commercial law, several important aspects of international commercial arbitration, and analyzes Karabelkov’s views on the main features of the listed arbitration. In addition, the important factors, reasons and procedures for appointing arbitrators are explored. In addition, the criteria for selection of a sole or presiding arbitrator are considered in the selection of an arbitrator. The article also discusses five important factors to consider when appointing an Arbitrator. Claudia Salmon’s thoughts on this are reviewed. The requirements and factors for appointing an arbitrator are reviewed, several studies are conducted, and suggestions are made about the mechanism of appointing an arbitrator.